2015
DOI: 10.1098/rsta.2014.0079
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response mitigation of floating wind turbine platforms using tuned liquid column dampers

Abstract: In this paper, we experimentally study and compare the effects of three combinations of multiple tuned liquid column dampers (MTLCDs) on the dynamic performance of a model floating tension-leg platform (TLP) structure in a wave basin. The structural stability and safety of the floating structure during operation and maintenance is of concern for the performance of a renewable energy device that it might be supporting. The dynamic responses of the structure should thus be limited for these renewable energy devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…waves (Jaksic et al, 2015b) for system identification or monitoring purposes. With the importance of offshore renewable energy recognised worldwide, a wide range of structural designs for wind and wave energy are extremely flexible and behave nonlinearly while in operation in the presence of high wind and wave.…”
Section: Discussion Related To Implementationmentioning
confidence: 99%
“…waves (Jaksic et al, 2015b) for system identification or monitoring purposes. With the importance of offshore renewable energy recognised worldwide, a wide range of structural designs for wind and wave energy are extremely flexible and behave nonlinearly while in operation in the presence of high wind and wave.…”
Section: Discussion Related To Implementationmentioning
confidence: 99%
“…Optimisation of control can then be carried out by carefully choosing the design parameters [13]. Recently, a number of studies on single and multiple TLCDs applied to onshore wind turbine towers and floating wind turbine platforms [14,15] have indicated that TLCDs may be a reasonable way to reduce wind turbine tower vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there have been efforts in developing different actuation schemes for stabilization and load reduction control for floating turbines, via both passive and active control. Colwell and Basu proposed the tuned liquid column damper (TLCD), and Jaksic et al evaluated 3 combinations of multiple TLCDs. Lackner and Rotea proposed to deploy the tuned‐mass damper (TMD) within the nacelle, evaluating the performance in reducing platform pitch and fatigue load under both passive and active control configurations.…”
Section: Introductionmentioning
confidence: 99%